2022
DOI: 10.1007/s13555-022-00748-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reducing Pigmentation by Collagen Peptide Intake: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Introduction:We examined the effect of 5.0 g/day of collagen peptide (CP) or collagen peptide fermented with Aspergillus sojae (FCP) on skin pigmentation in healthy participants. Methods: In this randomized, double-blind, placebo-controlled study, 44 men and women aged 25-63 years were placed into three groups by stratified random allocation and treated with CP, FCP, or placebo (PL) at 5.0 g/day for 3 months. Their skin condition was measured monthly from baseline to 3 months of intake. Results: No adverse eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
2
0
4
Order By: Relevance
“…For the lower layer, collagen was a significant factor as it significantly decreased erythema ( p -value < 0.05). Himeno et al [ 17 ] showed that collagen can reduce irritation because it decreases inflammation and also has a skin-remodeling function. PEG had a significant quadratic effect that increased the breaking strength because PEG, together with Kollicoat ® Protect, reduces the intermolecular forces of the polymer, increasing its mobility and allowing the polymer chains to move more freely, giving it greater flexibility and strength [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the lower layer, collagen was a significant factor as it significantly decreased erythema ( p -value < 0.05). Himeno et al [ 17 ] showed that collagen can reduce irritation because it decreases inflammation and also has a skin-remodeling function. PEG had a significant quadratic effect that increased the breaking strength because PEG, together with Kollicoat ® Protect, reduces the intermolecular forces of the polymer, increasing its mobility and allowing the polymer chains to move more freely, giving it greater flexibility and strength [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Application of these formulations decreases erythema compared with the control wound. This is due to the components of the formulations, such as D-panthenol and collagen, which have been shown to reduce inflammation and improve the healing process [ 17 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kemerahan dan pigmentasi pada kulit disebabkan oleh paparan sinar matahari. Berdasarkan studi Himeno et al (2022) kolagen peptida memiliki efek yang lebih baik dalam mengurangi kemerahan kulit dan pigmentasi lebih cepat dibanding kolagen peptida yang difermentasi (FCP), sedangkan pada Ito et al (2018) kolagen peptida dapat menurunkan kemerahan pada kulit [1], [15]. Namun dikarenakan studi yang dilakukan memiliki ukuran sampel yang kecil disamping banyak faktor yang dapat berkontribusi terhadap kemerahan kulit seperti faktor metabolisme dan usia atau faktor luar seperti gaya hidup (paparan UV, suhu dingin, penggunaan tabir surya, sauna, dan obat-obatan antihipertensi) maka studi lanjutan diperlukan.…”
Section: Manfaat Lain Kolagen Terhadap Kulitunclassified
“…Kolagen memiliki komposisi asam amino yang unik. Gabungan molekul kolagen ini membentuk kolagen fibril dengan berikatan silang (tripel heliks) dengan konfigurasi (Gli-X-Y)n dengan X dan Y biasanya prolin dan hidroksiprolin [14], [15]. Selanjutnya kolagen fibril ini bergabung untuk membentuk serat kolagen [1], [12].…”
unclassified
See 1 more Smart Citation